UTILIZATION OF LIBRARY SERVICES BY THE STUDENTS OF WOMEN ARTS AND SCIENCE COLLEGES IN CHENNAI - T. Rubanya; Dr. T. Prabakaran (The Bioscan, 2025)
Academic libraries are those that have been set up in higher education institutions with the dual goals of supporting faculty and student research as well as the curriculum of the school. The study's main focus was on the user experience and library services at Chennai's Women’s Arts and Science College libraries. The investigation was carried out using a survey with a questionnaire. The study included data from fifteen women's arts and science colleges. This study looks at how often students use the library, how satisfied they are with it, and what obstacles they have while trying to use it. This study found that Current awareness service, library websites, printer/scanner services and online database service are the most important library service used by the students.